Ternary monatomic alloy catalyst as well as preparation method and application thereof

By using a ternary single atom alloy catalyst in the CO-SCR catalyst, a catalyst with Rh single atom dispersed on the surface of the PdM alloy is prepared by using a high-temperature in situ inverse dispersion method, the problems of insufficient low-temperature activity and N2 selectivity of the existing catalyst are solved, and the effects of high-temperature stability and long-life are achieved.

CN119701999APending Publication Date: 2025-03-28CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621170.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing CO-SCR catalysts have poor performance in low-temperature activity and N2 selectivity, and are prone to inactivate at high temperatures, and the ratio of the active metal load to the support metal load is limited to about 1 to 2%, resulting in the failure of the stability and activity of the single-atom alloy catalyst to the full extent.

Method used

A ternary single atom alloy catalyst was used to prepare a catalyst dispersed on the surface of the PdM alloy in the form of Rh single atoms by high-temperature in situ inverse dispersion method. The Rh/Pd ratio exceeded 16%, the support was SUP, such as Al2O3, MgO, etc., and the loading amount was between 0.5% and 5% by weight.

Benefits of technology

The low-temperature activity and N2 selectivity of the catalyst were significantly improved. T50 and T90 were 160℃ and 200℃ respectively, and were kept at 350℃ for 100 hours without deactivation. After sintering at 800℃ for 10 hours, there was no obvious deactivation, which extended the life of the catalyst and reduced energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701999A_ABST
    Figure CN119701999A_ABST
Patent Text Reader

Abstract

The invention discloses a ternary monatomic alloy catalyst as well as a preparation method and application thereof, relates to the technical field of catalysts, and solves the problems that an existing denitration catalyst is low in low-temperature activity and N2 selectivity, easy to inactivate at high temperature and the like. The ternary monatomic alloy denitration catalyst is characterized in that active metal is dispersed on the surface of an alloy loaded by an inert carrier SUP in a monatomic form; the active metal is Rh; the alloy is PdM alloy, and M is selected from one of Zn, Cu, In, Fe, Co, Bi and Sn; the inert carrier SUP is Al2O3 (aluminum oxide), MgO (magnesium oxide), SiO2 (silicon dioxide), CeO2 (cerium oxide), La2O3 (lanthanum oxide), CoAl2O4 (cobalt oxide) The loading capacity of the alloy on the inert carrier is 0.5 wt%-5wt%; and the loading capacity of the active metal on the surface of the alloy is 1-16%. The catalyst can be applied to a three-way catalyst to catalytically reduce nitrogen oxide into N2, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a ternary single-atom alloy catalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides (NO x ) is the main factor of air pollution. Nitrogen oxides produced by automobile exhaust, thermal power generation and industrial waste gas not only cause serious environmental problems such as acid rain, photochemical smog, and ozone layer depletion, but also have serious impacts on the human respiratory system and cardiovascular system. In the context of sustainable development, countries around the world are increasingly tightening their policies on pollutant emissions. x The elimination process places higher demands.

[0003] NO x Selective catalytic reduction is the current mainstream denitrification technology, which uses NH3 and CO as reducing agents to catalytically convert NOx into harmless N2 at a certain temperature. Compared with the use of corrosive NH3 for selective catalytic reduction (NH3-SCR), the use of CO, which is also a component of exhaust gas, for reduction reaction (CO-SCR) not only reduces the complexity and cost of equipment and avoids the risk of NH3 leakage, but also achieves the effect of "treating waste with waste". Through a simple catalytic process, the two pollutants can be converted into harmless N2 and CO2, which has good application prospects.

[0004] When developing CO-SCR catalysts, metal alloy active centers can deeply fuse two or more metals, induce electronic effects, and combine the characteristics of different metals to produce new catalytic properties, thus having better catalytic performance. Among them, single-atom alloys are active metals dispersed in the form of single atoms on the surface of the carrier metal. This structure can not only improve the catalytic performance, but also make the single-atom component achieve 100% metal utilization, greatly reducing the cost of catalyst production.

[0005] However, in the preparation process of CO-SCR catalyst, due to the high surface energy of active metal atoms, the tendency of single atoms to agglomerate is greater than the tendency to disperse. Active metal atoms must overcome the high surface energy to prevent agglomeration, which requires that the surface active metal loading should not be too high. Usually, the molar ratio of active metal to carrier metal is below 5%, which seriously limits the optimization and practical application of single-atom alloy catalysts. For example, in the previous report, when preparing Pt / Cu single-atom alloy catalysts, when the molar ratio of Pt / Cu was 0.022, Pt was dispersed on the Cu surface in the form of single atoms. When the Pt / Cu ratio was increased to 0.12, Pt agglomerated into clusters and nanoparticles on the Cu surface. This limitation is more obvious at high temperatures. At high temperatures, due to more active atomic thermal motion, surface active atoms are more likely to agglomerate, resulting in poor stability. The easy agglomeration of active metals limits the full play of the activity and stability of single-atom alloy catalysts to a certain extent. For example, it is recorded in the Chinese patent document CN118360629A that when preparing Ag1-In single-atom alloy, in order to disperse Ag in the form of single atoms on the surface of In, the mass ratio of In2O3 and AgNO3 in the raw material needs to be limited to 100:1, and then AgNO3 is loaded on the surface of In2O3 and reduced by applying an external current to obtain the Ag1-In single-atom alloy structure. In another study, in order to load Pd single atoms on the surface of NiGa intermetallic compounds to prepare Pd1-NiGa single-atom alloy structure, the researchers controlled the molar ratio of Pd and Ni precursors to 0.014, and then used the 900-degree hydrogen reduction method to obtain Pd. I -NiGa single-atom alloy, however, when the molar ratio of Pd to Ni increases to 0.056, Pd aggregates into nanoparticles on the surface of NiGa alloy (Angew.Chem.Int.Ed.,2024,e202410979). From the above, it can be seen that in different single-atom alloy preparation methods, there is a common problem, that is, the ratio of active metal loading to carrier metal loading is limited to about 1-2%. Once it exceeds 5%, the active metal is easy to aggregate on the surface of the carrier metal and lose its structural advantage.

[0006] In addition, in the CO-SCR reaction, how to balance low-temperature activity and high-temperature stability and how to ensure 100% N2 selectivity are two urgent problems to be solved. On the one hand, as a basic reaction in three-way catalysis, the catalyst must not only ensure a good conversion rate when the car is cold started (temperature less than 200°C), but also avoid active metal sintering and catalyst deactivation in the high temperature environment of the engine (temperature greater than 800°C). On the other hand, NO xN2O generated by incomplete reduction will also cause greenhouse effect and air pollution that cannot be ignored. The CO-SCR catalysts reported so far are mainly Pd-based catalysts, which have low activity below 200°C, NO conversion rate below 20%, and N2 selectivity below 30%. For example, a series of Pd-based catalysts were prepared in the study (Chem. Sci., 2019, 10, 4148-4162), with NO conversion rates below 200°C and N2 selectivity below 40%. In addition to low-temperature activity and selectivity issues, high-temperature resistance to deactivation of the catalyst is also a very important indicator. Chinese patent document CN118634847A discloses a sintering-resistant ultra-high temperature denitrification catalyst. A BaCO3-modified perovskite BaZrO3 carrier is prepared by hydrothermal reaction and high-temperature calcination to replace the easily sintered TiO2 carrier, so that the carrier specific surface area remains unchanged during sintering at 700°C. Then, samarium salts and tungsten salts are loaded on the prepared carrier as active centers, so that the catalyst can achieve a denitrification efficiency of more than 95% at 450-500°C. However, so far, achieving metal deactivation resistance at 800°C is still a very difficult problem.

[0007] In summary, it is of great significance to develop CO-SCR single-atom alloy catalysts with a high active metal / inert metal ratio to improve low-temperature catalytic activity and N2 selectivity and inhibit single-atom agglomeration under high-temperature conditions. Summary of the invention

[0008] In order to solve the problems faced by existing denitration catalysts, such as low-temperature activity, low N2 selectivity, and easy deactivation of catalysts at high temperatures, the present invention proposes a ternary single-atom alloy catalyst and a preparation method and application thereof.

[0009] The technical solution of the present invention is as follows:

[0010] A ternary single-atom alloy catalyst, wherein the ternary single-atom alloy denitration catalyst is a catalyst in which active metals are dispersed in the form of single atoms on the surface of an alloy supported by an inert carrier SUP;

[0011] The active metal is Rh;

[0012] The alloy is a PdM alloy, wherein M is selected from one of Zn, Cu, In, Fe, Co, Bi, and Sn;

[0013] The inert carrier SUP is Al2O3, MgO, SiO2, CeO2, La2O3, CoAl2O4, CuAl2O4;

[0014] The loading amount of the alloy on the inert carrier SUP is 0.5wt% to 5wt%;

[0015] The loading amount of the active metal on the alloy surface is 1% to 16%.

[0016] The present invention also provides a method for preparing the above-mentioned ternary single-atom alloy catalyst, comprising the following steps:

[0017] Synthesis of S1 and PdM-SUP:

[0018] SUP was uniformly dispersed in deionized water by ultrasonication, H2PdCl4 solution and nitrate or chloride of M were added, dissolved uniformly, evaporated and impregnated after magnetic stirring, and the obtained solid was fully ground and reduced in reducing gas to obtain SUP-loaded PdM alloy particles PdM-SUP;

[0019] S2, Rh (纳米粒子) -Preparation of PdM-SUP ternary heterogeneous alloy:

[0020] The PdM-SUP obtained in step S1 was evenly dispersed in deionized water by ultrasonication, and Rh(NO3)3 solution was added dropwise, stirred, centrifuged and washed with water, and vacuum dried overnight to obtain a ternary heterogeneous alloy Rh loaded on the surface of the PdM alloy in the form of Rh nanoparticles. (纳米粒子) -PdM-SUP;

[0021] S3, Rh (单原子) -Preparation of PdM-SUP single atom alloy:

[0022] Take the product Rh in step S2 (单原子) -PdM-SUP was placed in a quartz tube and then placed in a fixed bed. A mixture of CO and NO was passed through the tube and the temperature was raised to 400°C to 850°C and maintained for 1h to 5h. After a high-temperature in-situ reverse dispersion process, a Rh-PdM ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdM alloy was obtained. (单原子) -PdM-SUP.

[0023] Preferably, the ratio of SUP to water in step S1 is 0.6 g to 1.2 g: 30 mL to 60 mL.

[0024] Preferably, the amount of H2PdCl4 solution used in step S1 is such that the concentration of Pd is 3wt%;

[0025] The molar amounts of the H2PdCl4 and nitrate or chloride are the same.

[0026] Preferably, the rotation speed of the magnetic stirring in step S1 is 1000 rpm, and the temperature of the evaporation and impregnation is 100°C.

[0027] Preferably, the reducing gas in step S1 is a 10% hydrogen-argon mixed gas at 600° C., and the reducing time is 0.5 h to 3 h.

[0028] Preferably, in step S2, the ratio of PdM-SUP to deionized water is 480 mg:150 mL, and the molar ratio of Rh(NO3)3 to H2PdCl4 is 0.01 to 0.16.

[0029] Preferably, in step S2, the stirring time is 3 hours, and the vacuum drying temperature is 80°C.

[0030] Preferably, the introduction rate of the mixed gas in step S3 is 100 mL / min, and the concentrations of CO and NO are both 1000 ppm.

[0031] The present invention also provides an application of the above-mentioned ternary single-atom alloy catalyst, which is specifically used for catalytic reduction of nitrogen oxides to generate N2 in a denitration reaction.

[0032] Compared with the prior art, the specific beneficial effects of the present invention are:

[0033] 1. Reduce energy consumption: The present invention utilizes a high-temperature in-situ induced reverse dispersion method to obtain a Rh-PdM single-atom alloy denitrification catalyst with a Rh / Pd ratio of more than 16%. The low-temperature activity and selectivity of the catalyst are greatly improved, with T50 (temperature at which 50% of NO is eliminated) and T90 (temperature at which 90% of NO is eliminated) being 160°C and 200°C, respectively, and showing very good N2 selectivity; the complete elimination reaction temperature can be reduced to about 225°C, greatly reducing the energy consumption during the reaction. At the same time, after Rh undergoes high-temperature reverse dispersion to form a single-atom alloy structure, it exhibits excellent stability, can remain undeactivated for 100 hours at 350°C, and does not undergo obvious deactivation after sintering at 800°C for 10 hours, which greatly improves the life of the catalyst and reduces the cost increase caused by catalyst replacement or regeneration.

[0034] 2. Save process steps: As a part of the three-way catalytic elementary reaction, the high-temperature reverse dispersion process in the catalyst synthesis process can be used as a simulation of the normal operating temperature of the three-way catalytic converter. When applied to three-way catalysis, no pretreatment is required in advance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is the XRD pattern of PdCu-Al2O3 in Example 1;

[0036] Figure 2 is the XRD pattern of PdIn-Al2O3 in Example 2;

[0037] Figure 3 is Rh in Example 3 (单原子) -XRD pattern of PdZn-Al2O3;

[0038] Figure 4 is Rh in Example 3 (纳米粒子) -PdZn-Al2O3 and Rh (单原子) -Infrared spectrum of carbon monoxide adsorption on PdZn-Al2O3;

[0039] Figure 5 is Rh in Example 3 (纳米粒子) -PdZn-Al2O3 and Rh (单原子) -TEM image of PdZn-Al2O3;

[0040] Figure 6 Rh (单原子) -PdZn-Al2O3, Rh (纳米粒子) - NO conversion results of PdZn-Al2O3 and comparative samples in CO-SCR catalytic reaction;

[0041] Figure 7 Rh (单原子) -PdZn-Al2O3, Rh (纳米粒子) - N2 selectivity results of PdZn-Al2O3 and comparative samples in CO-SCR catalytic reaction;

[0042] Figure 8 Rh (单原子) -PdZn-Al2O3 stability test results at 350℃ for 100h;

[0043] Fig. 9 Rh (单原子) -Cold start performance test results of PdZn-Al2O3 after aging at 800℃ for 10h. DETAILED DESCRIPTION

[0044] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0045] Example 1.

[0046] (1) 1.2 g of Al2O3 was placed in 60 mL of deionized water and dispersed evenly by ultrasonication for 20 min. 15 mL of H2PdCl4 solution (0.023 mol / L) and 135 mg of Cu(NO3)2·3H2O were added to dissolve and disperse evenly. After high-speed stirring at 1000 rpm for 3 h, the mixture was evaporated and impregnated at 100°C. After sufficient grinding, the solid was reduced in a 10% hydrogen-argon mixture at 600°C for 2 h to obtain Al2O3-loaded PdCu alloy particles PdCu-Al2O3. Figure 1This is the XRD pattern of PdCu-Al2O3. The PdCu alloy peak corresponds exactly to the PDF standard card, proving the successful synthesis of PdCu-Al2O3.

[0047] (2) 480 mg of the PdCu-Al2O3 prepared in step (1) was dispersed in 150 mL of water and transferred to a 250 mL three-necked flask. The mixture was evenly dispersed by ultrasonication for 15 min. 0.2 mL of Rh(NO3)3 solution (0.1 mol / L) was dropwise injected into the flask. After stirring for 3 h, the mixture was centrifuged and washed with water. The mixture was vacuum dried at 80 °C overnight to obtain a ternary heterogeneous alloy Rh in which Rh was loaded on the surface of the PdCu alloy in the form of nanoparticles. (纳米粒子) -PdCu-Al2O3.

[0048] (3) Take Rh (纳米粒子) -PdCu-Al2O3 ternary alloy was placed in a quartz tube and then placed in a fixed bed. A mixed gas of 100 mL / min CO (1000 ppm) and NO (1000 ppm) was passed through the tube. The temperature was raised to 600 °C and maintained for 2 h. After a high-temperature in-situ reverse dispersion process, a Rh-PdCu ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdCu alloy was obtained. (单原子) -PdCu-Al2O3.

[0049] Example 2.

[0050] (1) 1.2 g of Al2O3 was placed in 60 mL of deionized water and dispersed evenly by ultrasonication for 20 min. 15 mL of H2PdCl4 solution (0.023 mol / L) and 120 mg of In(NO3)3·4.5H2O were added to dissolve and disperse evenly. After high-speed stirring at 1000 rpm for 3 h, the mixture was evaporated and impregnated at 100°C. After sufficient grinding, the obtained solid was reduced in a 10% hydrogen-argon mixture at 600°C for 2 h to obtain Al2O3-loaded PdIn alloy particles PdIn-Al2O3. Figure 2 This is the XRD pattern of PdIn-Al2O3. The PdIn alloy peak corresponds exactly to the PDF standard card, proving the successful synthesis of PdIn-Al2O3.

[0051] (2) 480 mg of the PdIn-Al2O3 prepared in step (1) was dispersed in 150 mL of water and transferred to a 250 mL three-necked flask. The mixture was dispersed evenly by ultrasonication for 15 min. 0.2 mL of Rh(NO3)3 solution (0.1 mol / L) was dropwise injected into the flask. After stirring for 3 h, the mixture was centrifuged and washed with water. The mixture was vacuum dried at 80 °C overnight to obtain a ternary heterogeneous alloy Rh loaded on the surface of the PdCu alloy in the form of Rh nanoparticles. (纳米粒子) -PdCu-Al2O3.

[0052] (3) Take Rh (纳米粒子) -PdIn-Al2O3 ternary alloy was placed in a quartz tube and then placed in a fixed bed. A mixed gas of 100 mL / min CO (1000 ppm) and NO (1000 ppm) was passed through the tube. The temperature was raised to 600 °C and maintained for 2 h. After a high-temperature in-situ reverse dispersion process, a Rh-PdIn ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdIn alloy was obtained. (单原子) -PdIn-Al2O3.

[0053] Example 3.

[0054] (1) 1.2 g of Al2O3 was placed in 60 mL of deionized water and dispersed evenly by ultrasonication for 20 min. 15 mL of H2PdCl4 solution (0.023 mol / L) and 161 mg of Zn(NO3)2·6H2O were added to dissolve and disperse evenly. After high-speed stirring at 1000 rpm for 3 h, the mixture was evaporated and impregnated at 100°C. After sufficient grinding, the solid was reduced in a 10% hydrogen-argon mixture at 600°C for 2 h to obtain Al2O3-loaded PdZn alloy particles PdZn-Al2O3.

[0055] (2) 480 mg of the PdZn-Al2O3 prepared in step (1) was dispersed in 150 mL of water and transferred to a 250 mL three-necked flask. The mixture was dispersed evenly by ultrasonication for 15 min. 0.2 mL of Rh(NO3)3 solution (0.1 mol / L) was dropwise injected into the flask. After stirring for 3 h, the mixture was centrifuged and washed with water. The mixture was vacuum dried at 80 °C overnight to obtain a ternary heterogeneous alloy Rh in which Rh was loaded on the surface of the PdZn alloy in the form of nanoparticles. (纳米粒子) -PdZn-Al2O3.

[0056] (3) Take Rh (纳米粒子) -PdZn-Al2O3 ternary alloy was placed in a quartz tube and then placed in a fixed bed. A mixed gas of 100 mL / min CO (1000 ppm) and NO (1000 ppm) was passed through the tube. The temperature was raised to 600 °C and maintained for 2 h. After a high-temperature in-situ reverse dispersion process, a Rh-PdZn ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdZn alloy was obtained. (单原子) -PdZn-Al2O3. Figure 3 Rh (单原子) -XRD pattern of PdZn-Al2O3, the PdZn alloy peak accurately corresponds to the standard peak of the PDF standard card, proving the successful synthesis of the PdZn alloy, and the metal peak of Rh disappears, proving that the size of Rh is below the XRD detection limit. Figure 5 This is the infrared spectrum of CO adsorption. It can be clearly seen from the figure that Rh (单原子)The Rh nanoparticle peak in the PdZn-Al2O3 disappeared, and the single atom peak appeared, proving that this example successfully prepared the Rh-PdZn ternary single atom alloy catalyst Rh with single atoms dispersed on the surface of the PdZn alloy. (单原子) -PdZn-Al2O3. Figure 5 Rh (纳米粒子) -PdZn-Al2O3 and Rh (单原子) -TEM image of PdZn-Al2O3, proving that PdZn alloy nanoparticles were successfully loaded on the Al2O3 surface.

[0057] Example 4.

[0058] (1) 1.2 g of MgO was placed in 60 mL of deionized water and dispersed evenly by ultrasonication for 20 min. 15 mL of H2PdCl4 solution (0.023 mol / L) and 161 mg of Zn(NO3)2·6H2O were added to dissolve and disperse evenly. After high-speed stirring at 1000 rpm for 3 h, the mixture was evaporated and impregnated at 100°C. After sufficient grinding, the solid was reduced in a 10% hydrogen-argon mixture at 600°C for 2 h to obtain MgO-loaded PdZn alloy particles PdZn-MgO.

[0059] (2) 480 mg of the PdZn-MgO prepared in step (1) was dispersed in 150 mL of water and transferred to a 250 mL three-necked flask. The mixture was evenly dispersed by ultrasonication for 15 min. 0.2 mL of Rh(NO3)3 solution (0.1 mol / L) was dropwise injected into the flask. After stirring for 3 h, the mixture was centrifuged and washed with water. The mixture was vacuum dried at 80 °C overnight to obtain a ternary heterogeneous alloy Rh in which Rh was loaded on the surface of the PdZn alloy in the form of nanoparticles. (纳米粒子) -PdZn-MgO.

[0060] (3) Take Rh (纳米粒子) -PdZn-MgO ternary alloy was placed in a quartz tube and then placed in a fixed bed. A mixed gas of 100 mL / min CO (1000 ppm) and NO (1000 ppm) was passed through the tube. The temperature was raised to 600 °C and maintained for 2 h. After a high-temperature in-situ reverse dispersion process, a Rh-PdZn ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdZn alloy was obtained. (单原子) -PdZn-MgO.

[0061] Example 5.

[0062] (1) 1.2 g of CeO2 was placed in 60 mL of deionized water and dispersed evenly by ultrasonication for 20 min. 15 mL of H2PdCl4 solution (0.023 mol / L) and 161 mg of Zn(NO3)2·6H2O were added to dissolve and disperse evenly. After high-speed stirring at 1000 rpm for 3 h, the mixture was evaporated and impregnated at 100°C. After sufficient grinding, the solid was reduced in a 10% hydrogen-argon mixture at 600°C for 2 h to obtain CeO2-loaded PdZn alloy particles PdZn-CeO2.

[0063] (2) 480 mg of the PdZn-CeO2 prepared in step (1) was dispersed in 150 mL of water and transferred to a 250 mL three-necked flask. The mixture was evenly dispersed by ultrasonication for 15 min. 0.2 mL of Rh(NO3)3 solution (0.1 mol / L) was dropwise injected into the flask. After stirring for 3 h, the mixture was centrifuged and washed with water. The mixture was vacuum dried at 80 °C overnight to obtain a ternary heterogeneous alloy Rh in which Rh was loaded on the surface of the PdZn alloy in the form of nanoparticles. (纳米粒子) -PdZn-CeO2.

[0064] (3) Take Rh (纳米粒子) -PdZn-CeO2 ternary alloy was placed in a quartz tube and then placed in a fixed bed. A mixed gas of 100 mL / min CO (1000 ppm) and NO (1000 ppm) was passed through the tube. The temperature was raised to 600 °C and maintained for 2 h. After a high-temperature in-situ reverse dispersion process, a Rh-PdZn ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdZn alloy was obtained. (单原子) -PdZn-CeO2.

[0065] Effect example 1.

[0066] Test the Rh obtained in Example 3 (单原子) -PdZn-Al2O3, Rh (单原子) -NO conversion rate of PdZn-Al2O3 and comparative sample PdZn-Al2O3 in CO-SCR catalytic reaction:

[0067] Test process: 50-275°C, 100mL / min, CO 1000ppm, NO 1000ppm, Ar gas balance.

[0068] Test results see Figure 6 The results showed that Rh (单原子) -The low-temperature activity of PdZn-Al2O3 is greatly improved, with T50 and T90 being around 160°C and 200°C respectively, so that the complete elimination reaction temperature can be reduced to below 225°C, greatly reducing the energy consumption during the reaction.

[0069] Effect example 2.

[0070] Test the Rh obtained in Example 3 (单原子) -PdZn-Al2O3, Rh (单原子) -PdZn-Al2O3 and the comparative sample PdZn-Al2O3 in the CO-SCR catalytic reaction. The results are calculated by the NO conversion rate and N2O by-product concentration obtained during the test of Effect Example 1.

[0071] Test results see Figure 7 The results showed that Rh (单原子) -PdZn-Al2O3 exhibits very good N2 selectivity, which avoids the incomplete reduction of nitrogen oxides to form N2O, causing non-negligible greenhouse effect and air pollution problems.

[0072] Effect example 3.

[0073] Test the Rh obtained in Example 3 (单原子) -PdZn-Al2O3 stability, cycled at 350℃ for 100h, test results see Figure 8 The N2 selectivity and NO conversion of the catalyst were almost unchanged. After sintering at 800℃ for 10h, the cold start performance was tested. Fig. 9 As shown in the figure, the catalyst has no obvious deactivation. The catalyst shows excellent stability, which greatly improves the life of the catalyst and reduces the cost increase caused by catalyst replacement or regeneration.

[0074] The present invention provides a ternary single-atom alloy catalyst and a preparation method and application thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A ternary single-atom alloy catalyst, characterized in that: The ternary single-atom alloy denitration catalyst is a catalyst in which the active metal is dispersed in the form of single atoms on the surface of the alloy supported by the inert carrier SUP; The active metal is Rh; The alloy is a PdM alloy, wherein M is selected from one of Zn, Cu, In, Fe, Co, Bi, and Sn; The inert carrier SUP is Al2O3, MgO, SiO2, CeO2, La2O3, CoAl2O4, CuAl2O4; The loading amount of the alloy on the inert carrier SUP is 0.5wt% to 5wt%; The loading amount of the active metal on the alloy surface is 1% to 16%.

2. A method for preparing the ternary single-atom alloy catalyst as claimed in claim 1, characterized in that: The steps include: Synthesis of S1 and PdM-SUP: SUP was evenly dispersed in deionized water by ultrasonication, and H2PdCl4 solution and nitrate or chloride of M were added to dissolve evenly, and then evaporated and impregnated after magnetic stirring. The obtained solid was fully ground and reduced in reducing gas to obtain SUP-loaded PdM alloy particles PdM-SUP; S2, Rh (纳米粒子) -Preparation of PdM-SUP ternary heterogeneous alloy: The PdM-SUP obtained in step S1 was evenly dispersed in deionized water by ultrasonication, and Rh(NO3)3 solution was added dropwise, stirred, centrifuged and washed with water, and vacuum dried overnight to obtain a ternary heterogeneous alloy Rh loaded on the surface of the PdM alloy in the form of Rh nanoparticles. (纳米粒子) -PdM-SUP; S3, Rh (单原子) -Preparation of PdM-SUP single atom alloy: Take the product Rh in step S2 (单原子) -PdM-SUP was placed in a quartz tube and then placed in a fixed bed. A mixture of CO and NO was passed through the tube and the temperature was raised to 400°C to 850°C and maintained for 1h to 5h. After a high-temperature in-situ reverse dispersion process, a Rh-PdM ternary single-atom alloy catalyst Rh with single-atom Rh dispersed on the surface of the PdM alloy was obtained. (单原子) -PdM-SUP.

3. The method for preparing the ternary single-atom alloy catalyst according to claim 2, characterized in that: The ratio of SUP to water in step S1 is 0.6 g to 1.2 g: 30 mL to 60 mL.

4. The method for preparing the ternary single-atom alloy catalyst according to claim 2, characterized in that: The amount of H2PdCl4 solution used in step S1 is such that the Pd content is 3 wt%; The molar amounts of the H2PdCl4 and nitrate or chloride are the same.

5. The method for preparing the ternary single-atom alloy catalyst according to claim 2, characterized in that: The rotation speed of the magnetic stirring in step S1 is 1000 rpm, and the temperature of the evaporation and impregnation is 100°C.

6. The method for preparing the ternary single-atom alloy catalyst according to claim 2, characterized in that: In step S1, the reducing gas is a 10% hydrogen-argon mixed gas at 600° C., and the reducing time is 0.5 h to 3 h.

7. The method for preparing a ternary single-atom alloy catalyst according to claim 2, characterized in that: In step S2, the ratio of PdM-SUP to deionized water is 480 mg:150 mL, and the molar ratio of Rh(NO3)3 to H2PdCl4 is 0.01 to 0.

16.

8. The method for preparing a ternary single-atom alloy catalyst according to claim 2, characterized in that: The stirring time in step S2 is 3 hours, and the vacuum drying temperature is 80°C.

9. The method for preparing a ternary single-atom alloy catalyst according to claim 2, characterized in that: In step S3, the introduction rate of the mixed gas is 100 mL / min, and the concentrations of CO and NO are both 1000 ppm.

10. Use of the ternary single-atom alloy catalyst according to claim 1 or the ternary single-atom alloy catalyst prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Used in the denitrification reaction to catalyze the reduction of nitrogen oxides to generate N2.

Citation Information

Patent Citations

  • Op-Ag1In monatomic alloy electrocatalyst as well as preparation method and application thereof

    CN118360629A

  • Sintering-resistant ultrahigh-temperature denitration catalyst and preparation method thereof

    CN118634847A